Network pharmacology analysis and experimental validation elucidate the protective mechanisms of BYHWD against hypoxia/reoxygenation-induced endothelial cell injury - Shi, Yan; Zhu, Qingnan; Zhou, Yue; Guan, Qing; Wen, Qingsi; Sun, Yu; Yan, Zewen; Li, Yuye; Zhao, Yangjianing; Liu, Lu; Lin, Hongli; Wang, Dapeng (Frontiers in Medicine, 2025)
ObjectiveAcute kidney injury (AKI) is a critical clinical condition with high mortality, and specific therapeutic drugs are currently lacking. Although Buyang Huanwu Decoction (BYHWD) has shown clinical efficacy against AKI, its underlying mechanisms remain unclear. This study integrated network pharmacology, in vitro experiments, and animal models to systematically elucidate the potential targets and signaling pathways of BYHWD in treating AKI, and to validate its protective effects on hypoxia/reoxygenation (H/R)-induced endothelial cell injury and renal ischemia-reperfusion injury (IRI) in vivo.MethodsActive components and putative targets of BYHWD were screened using network pharmacology, and their intersections with AKI-related disease targets were identified. Protein-protein interaction (PPI) analysis, Gene Ontology and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, and molecular docking were performed. An in vitro H/R injury model was established using human umbilical vein endothelial cells (HUVECs). Cell counting kit-8 (CCK-8), trypan blue staining, flow cytometry, and Western blot were applied to assess the effects of BYHWD-containing serum on cell proliferation, apoptosis, oxidative stress, and the expression of proteins related to the VEGFRII/PI3K/AKT/FOXO1 pathway. For in vivo validation, a rat model of AKI was established via renal IRI. Rats were randomly divided into sham, IRI model, and BYHWD treatment groups. Renal function was assessed by measuring serum creatinine (SCr) and blood urea nitrogen levels. Renal histopathological changes were evaluated by hematoxylin and eosin (H&E) and Periodic Acid-Schiff staining.ResultsNetwork pharmacology identified 133 active components in BYHWD and 210 overlapping drug-disease targets. PPI analysis revealed hub genes including VEGFA, AKT1, IL6, and TP53. KEGG enrichment analysis highlighted the PI3K-AKT signaling pathway as a central pathway. Molecular docking demonstrated stable binding of luteolin and quercetin to VEGFA. In vitro experiments confirmed that BYHWD-containing serum increased HUVECs viability, inhibited apoptosis, reduced ROS levels, and modulated the protein expression of Bax/Bcl-2, MCP-1, α-SMA, and CD31. Furthermore, BYHWD activated VEGFRII and the downstream PI3K/AKT/FOXO1 pathway. In animal experiments, BYHWD treatment significantly ameliorated renal dysfunction in IRI-induced AKI rats, as evidenced by decreased SCr and BUN levels. Histopathological examination showed that BYHWD attenuated tubular injury, necrosis, and cast formation.ConclusionBYHWD may alleviate H/R-induced endothelial cell injury by suppressing oxidative stress and apoptosis through active components such as luteolin and quercetin, which target key genes including VEGFA and AKT1, thereby activating the PI3K/AKT/FOXO1 signaling pathway. This study provides integrated experimental evidence from network pharmacology, in vitro, and in vivo studies, supporting the use of BYHWD in AKI treatment.